2016
DOI: 10.1130/ges01268.1
|View full text |Cite
|
Sign up to set email alerts
|

Southeastern Atlantic deep-water evolution during the late-middle Eocene to earliest Oligocene (Ocean Drilling Program Site 1263 and Deep Sea Drilling Project Site 366)

Abstract: Comparison of new benthic foraminiferal δ 18 O and δ 13 C records from Ocean Drilling Program (ODP) Site 1263 (Walvis Ridge, southeast Atlantic, 2100 m paleodepth) and Deep Sea Drilling Project (DSDP) Site 366 (Sierra Leone Rise, eastern equatorial Atlantic, 2200-2800 m paleodepth) with published data from Atlantic and Southern Ocean sites provides the means to reconstruct the development of deep-water circulation in the southeastern Atlantic from the late-middle Eocene to the earliest Oligocene. Our compariso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 113 publications
(239 reference statements)
0
29
0
Order By: Relevance
“…An increase in the flux of NCW into the Southern Ocean would cause a decrease in ε Nd ( t ) values into the Oligocene, due to the mixing of unradiogenic NCW ( ɛ Nd = −10.07 ± 0.10; ferromanganese crust sample ALV‐539; O'nions et al, ) with proto‐CDW (i.e., ε Nd ( t ) = −7.5 to −8 in the late Eocene; Scher et al, ). Comparison of benthic foraminiferal δ 18 O records suggests the inception of NCW formation around the middle to late Eocene (~38.5 Ma) in the Labrador Sea (Borrelli et al, ), strengthening around 35 Ma (Langton et al, ). The presence of NCW in the deep Atlantic by the earliest Oligocene is also supported by the onset of drift deposition in the northeast Atlantic (Davies et al, ) and δ 13 C deep‐water aging gradients (Elsworth et al, ), though Abelson and Erez () suggest NCW and the onset of modern‐like Atlantic meridional overturning circulation (AMOC) occurred during the late Eocene, immediately before the EOT.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in the flux of NCW into the Southern Ocean would cause a decrease in ε Nd ( t ) values into the Oligocene, due to the mixing of unradiogenic NCW ( ɛ Nd = −10.07 ± 0.10; ferromanganese crust sample ALV‐539; O'nions et al, ) with proto‐CDW (i.e., ε Nd ( t ) = −7.5 to −8 in the late Eocene; Scher et al, ). Comparison of benthic foraminiferal δ 18 O records suggests the inception of NCW formation around the middle to late Eocene (~38.5 Ma) in the Labrador Sea (Borrelli et al, ), strengthening around 35 Ma (Langton et al, ). The presence of NCW in the deep Atlantic by the earliest Oligocene is also supported by the onset of drift deposition in the northeast Atlantic (Davies et al, ) and δ 13 C deep‐water aging gradients (Elsworth et al, ), though Abelson and Erez () suggest NCW and the onset of modern‐like Atlantic meridional overturning circulation (AMOC) occurred during the late Eocene, immediately before the EOT.…”
Section: Discussionmentioning
confidence: 99%
“…This was occurring at a time when equatorial seaways (i.e., Panama and Tethys) were still open, allowing water mass flow from the Atlantic to Pacific Oceans. Foraminiferal studies have suggested a warm, saline deepwater mass existed during the Eocene and Oligocene in the Atlantic and Pacific Oceans and had a low‐latitude source [ Borrelli and Katz , ; Kennett and Stott , ; Langton et al , ; Mead et al , ; Pak and Miller , ; Pekar et al , ; Via and Thomas , ].…”
Section: Discussionmentioning
confidence: 99%
“…This gradient began developing in the middle Eocene [ Cramer et al , ], reaching full extent in the early Oligocene. The development of this gradient has been linked to the strengthening and deepening of the Antarctic Circumpolar Current (ACC) during the late Eocene to early Oligocene [ Borrelli et al , ; Borrelli and Katz , ; Cramer et al , ; Katz et al , ; Langton et al , ; Scher et al , ; Scher and Martin , ], and development of a multilayered ocean structure by ~30 Ma as the high‐latitude Southern Ocean became thermally isolated [ Cramer et al , ; Katz et al , ; Scher et al , ]. This led to a differentiation between southern and northern deepwater sources [ Via and Thomas , ] and allowed the Atlantic and Pacific Ocean basins to be bathed by a new bottom water mass while the Southern Ocean became isolated and homogenized [ Scher et al , ].…”
Section: Introductionmentioning
confidence: 99%
“…In the Atlantic Ocean, several studies have documented thermal differentiation between the North and South Atlantic with an~2°C cooling of southern high latitudes, represented by añ 0.5‰ δ 18 O bf difference, starting between 38.5 and 35 Ma (Borrelli et al, 2014;Coxall et al, 2018;Cramer et al, 2009;Katz et al, 2011;Langton et al, 2016;Liu et al, 2018). Southern Hemisphere cooling in the Atlantic basin has often been interpreted as an indicator of the onset of a proto-ACC and of a decreased southward OHT (Borrelli et al, 2014;Katz et al, 2011;Langton et al, 2016). Borrelli et al (2014) further describe brief warming of North Atlantic deep waters occurring contemporaneously to the thermal differentiation (~38.5 Ma) and interpret this warming as the signature of deepwater formation in the Northern Hemisphere.…”
Section: Intermediate/deep Ocean Changesmentioning
confidence: 99%
“…Further, DP opening is often correlated with the contemporaneous onset of a marked difference between northern and southern latitude temperatures in the Atlantic Ocean, with cooler temperatures in the high southern latitudes suggested by δ 18 O data (Borrelli et al, 2014;Coxall et al, 2018;Cramer et al, 2009;Katz et al, 2011;Langton et al, 2016). On the other hand, different proxies (δ 13 C, εNd, δ 18 O, and contourites) suggest the onset of North Atlantic Deep Water formation (NADW) during the late Eocene, which may also have contributed to the thermal differentiation mentioned above (Borrelli et al, 2014;Coxall et al, 2018;Hohbein et al, 2012;Katz et al, 2011;Langton et al, 2016;Scher & Martin, 2008).…”
Section: Introductionmentioning
confidence: 99%